Synthesis and Biological Evaluation of Novel Isoxazole-Amide Analogues as Anticancer and Antioxidant Agents. (9th March 2021) - Eid, Ahmad M.; Hawash, Mohammed; Amer, Johnny; Jarrar, Abdullah; Qadri, Samira; Alnimer, Iman; Sharaf, Aya; Zalmoot, Raya; Hammoudie, Osama; Hameedi, Saba; Mousa, Ahmed
Abstract : Cancer now is one of the leading causes of mortality in the world. There has been a lot of effort to discover new anticarcinogenic agents that allow treatment with fewer side effects. A series of isoxazole-carboxamide derivatives (2a –2g ) were synthesised and evaluated for their cytotoxic activity against breast (MCF-7), cervical (HeLa), and liver (Hep3B) cancer cell lines and their antioxidant activity in the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. The results showed that 2d and 2e were the most active compounds against Hep3B cells, with a half-maximal inhibitory concentration (IC50 ) of around 23 μ g/ml; 2d showed the highest activity against HeLa cells, with an IC50 15.48 μ g/ml. However, 2a had the lowest IC50 (39.80 μ g/ml) against MCF-7 cells. By contrast, compound 2 g was inactive against all cancer cell lines, with IC50 values >400 μ g/ml. Both 2d and 2e reduced Hep3B secretion of alpha-fetoprotein (to 1829.33 ± 65.91 ng / ml and 1758.66 ± 54.04 ng / ml, respectively). Furthermore, in cell cycle analysis, 2d and 2e induced a delay in the G2/M phase of 18.07%, which is similar to the doxorubicin positive control. Moreover, 2d and 2e reduced the necrosis rate of Hep3B threefold and instead shifted the cells to apoptosis. Our results indicate that 2d and 2e have potent and promising anticancer activity. However, compound 2a was the most active as antioxidant agent (I C 50 = 7.8 ± 1.21 μ g / ml ) compared with Trolox as a positive control (IC50 2.75 μ g/ml).